2024
DOI: 10.14336/ad.2023.0514
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Microglia in Brain Metastases: Mechanisms and Strategies

Abstract: Brain metastases and related complications are one of the major fatal factors in cancer. Patients with breast cancer, lung cancer, and melanoma are at a high risk of developing brain metastases. However, the mechanisms underlying the brain metastatic cascade remain poorly understood. Microglia, one of the major resident macrophages in the brain parenchyma, are involved in multiple processes associated with brain metastasis, including inflammation, angiogenesis, and immune modulation. They also closely interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 150 publications
(149 reference statements)
0
1
0
Order By: Relevance
“…During cancer progression, microglia cells polarize in different phenotypes: the M1 phenotype induces reactive oxygen species (ROS) and nitric oxide (NO) and releases proinflammatory cytokines (IL-1 β, IL-6, TNF α, CCL2), resulting in anti-tumor effects [46][47][48]; the M2 phenotype regulates anti-inflammatory cytokine secretion (TGF-β and IL-10) as well as immunosuppressive factors (ARG-1 and CD36), leading to pro-tumor consequences [49][50][51]. Several studies have demonstrated that glioma-associated microglia show both phenotypes in human GBM specimens, and distinguishing between these two phenotypes is very difficult [52,53].…”
Section: Human Gbm and Microgliamentioning
confidence: 99%
“…During cancer progression, microglia cells polarize in different phenotypes: the M1 phenotype induces reactive oxygen species (ROS) and nitric oxide (NO) and releases proinflammatory cytokines (IL-1 β, IL-6, TNF α, CCL2), resulting in anti-tumor effects [46][47][48]; the M2 phenotype regulates anti-inflammatory cytokine secretion (TGF-β and IL-10) as well as immunosuppressive factors (ARG-1 and CD36), leading to pro-tumor consequences [49][50][51]. Several studies have demonstrated that glioma-associated microglia show both phenotypes in human GBM specimens, and distinguishing between these two phenotypes is very difficult [52,53].…”
Section: Human Gbm and Microgliamentioning
confidence: 99%